Effect of different levels of Dhania seed (Coriandrum sativum) on the performance of broiler (Bangladesh Journal of Animal Science, 2014)
A total of 72 as hatched Cobb 500 broilers were fed ad libitum on a diet with 0 %, 0.5 %, 1.0 % and 1.5 % of coriander seed meal (CSM) to assess its feeding value. Treatment group with 1.5 % of CSM significantly (p